A literature revision in primary cutaneous B-cell lymphoma - R La Selva; S Alberti Violetti; C Delfino; V Grandi; S Cicchelli; C Tomasini; MT Fierro; E Berti; N Pimpinelli; P Quaglino (Wolters Kluwer Medknow Publications, 2017)
The term "Primary Cutaneous B-Cell Lymphoma" (PCBCL) comprehends a variety of lymphoproliferative disorders characterized by a clonal proliferation of B-cells primarily involving the skin. The absence of evident extra-cutaneous disease must be confirmed after six-month follow-up in order to exclude a nodal non-Hodgkin's lymphoma (NHL) with secondary cutaneous involvement, which may have a completely different clinical behavior and prognosis. In this article, we have summarized the clinico-pathological features of main types of PCBCL and we outline the guidelines for management based on a review of the available literature.